HIGHWAY 1 RAT CREEK EMBANKMENT FAILURE;2021 RECONNAISSANCE AND ANALYSIS - EMBANKMENTS, DAMS, AND SLOPES TECHNICAL COMMITTEE (AMERICAN SOCIETY OF CIVIL, 2023)
GSP 337 provides an overview of the reconnaissance and analysis done of the embankment failure caused by Rat Creek onto Highway 1 in Northern California.